2003
DOI: 10.1107/s1600536803000722
|View full text |Cite
|
Sign up to set email alerts
|

N-[3,5-Bis(trifluoromethyl)phenyl]salicylaldimine

Abstract: Key indicatorsSingle-crystal X-ray study T = 180 K Mean '(C±C) = 0.005 A Ê Disorder in main residue R factor = 0.063 wR factor = 0.191 Data-to-parameter ratio = 9.5For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
4
9
0
Order By: Relevance
“…An ORTEP-3 (Farrugia, 1997) plot of the molecule of (I) is shown in Fig.1. The C8-N1 and C1-C7 bond lengths are 1.426 (3) and 1.450 (3) Å, respectively (Table 1) to the corresponding bond length in N- [3,5-bis(trifluoromethyl)phenyl]salicylaldimine [1.276 (4) Å; Karadayı et al, 2003].…”
supporting
confidence: 64%
See 1 more Smart Citation
“…An ORTEP-3 (Farrugia, 1997) plot of the molecule of (I) is shown in Fig.1. The C8-N1 and C1-C7 bond lengths are 1.426 (3) and 1.450 (3) Å, respectively (Table 1) to the corresponding bond length in N- [3,5-bis(trifluoromethyl)phenyl]salicylaldimine [1.276 (4) Å; Karadayı et al, 2003].…”
supporting
confidence: 64%
“…The O1···N1 distance of 2.609 (3) Å is comparable to those observed for analogous hydrogen bonds in N-[3,5bis(trifluoromethyl)phenyl]salicylaldimine [2.604 (4) Å; Karadayı et al, 2003] and 2,2-salicylaldimine [2.611 (6) Å; Xu et al, 1994].…”
mentioning
confidence: 99%
“…o-Hydroxyarylidene Schiff bases demonstrate two possible tautomeric forms, keto-amine and phenol-imine. In the solid state, the keto-amine tautomer has been established in naphthaldimine compounds (Hö kelek et al, 2000;Ü nver et al, 2002) while the phenol-imine tautomer is found in salicylaldimine Schiff bases (Dey et al, 2001;Yang & Vittal, 2003;Karadayı et al, 2003). Against this background, we present here the crystal structure of the title compound, (I).…”
Section: Commentmentioning
confidence: 95%
“…The C8-N1 and C7-C6 bond lengths are 1.418 (5) and 1.454 (5) Å , respectively (Table 1), and agree with the corresponding distances in 2-[(4-hydroxyphenyl)iminomethyl]thiophene [1.422 (2) and 1.447 (3) Å , respectively; Kazak et al, 2000], trans-4-[(4-dimethylaminophenyl)iminomethyl]-N-methylpyridinium para-toluenesulfonate [1.413 (3) and 1.461 Å , respectively; Coe et al, 2001], N-[3,5-bis(trifluoromethyl)phenyl]salicylaldimine [1.417 (4) and 1.439 (4) Å , respectively; Karadayı et al, 2003] and N-[3,5-bis(trifluoromethyl)phenyl]-3-methoxysalicylaldimine [1.412 (4) and 1.442 (4) Å , respectively; Karadayı et al, 2003]. The N1 C7 bond length of 1.270 (5) Å is typical of a double bond, similar to the corresponding bond lengths in N-(2,4dinitrophenyl)-N-methylhydrazone [1.279 (2) Å ; Aygü n et al, 1998], 2-salicylideneamino-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carbonitrile [1.281 (2) Å ; Elerman & Elmalı, 1998] and N-[3,5-bis(trifluoromethyl)phenyl]salicylaldimine [1.276 (4) Å ; Karadayı et al, 2003]. The O1-C5 and O2-C4 bond lengths are 1.346 (4) and 1.367 (4) Å , respectively, and agree with the corresponding distances in 2-{[tris(hydroxymethyl)methyl]aminomethylene}cyclohexa-3,5-dien-1(2H)one and its 6-hydroxy and 6-methoxy derivatives [1.3025 (16) and 1.3684 (19) Å , respectively; Odabaşoǧ lu et al, 2003].…”
Section: Commentmentioning
confidence: 99%
“…o-Hydroxyarylidene Schiff bases display two possible tautomeric forms, namely, phenol-imine and keto-amine. In the solid state, the keto-amine tautomer has been found in naphthaldimine (Hö kelek et al, 2000;Ü nver et al, 2002), while the phenol-imine tautomer is found in salicylaldimine Schiff bases (Yıldız et al, 1998;Elmalı & Elerman, 1998;Dey et al, 2001;Yang & Vittal, 2003;Karadayı et al, 2003).…”
Section: Commentmentioning
confidence: 99%